Pharmacokinetics of Etravirine Combined with Atazanavir/Ritonavir and a Nucleoside Reverse Transcriptase Inhibitor in Antiretroviral Treatment-Experienced, HIV-1-Infected Patients. (15th January 2015) - Orrell, Catherine; Felizarta, Franco; Nell, André; Kakuda, Thomas N.; Lavreys, Ludo; Nijs, Steven; Tambuyzer, Lotke; Van Solingen-Ristea, Rodica; Tomaka, Frank L.
Abstract : Objectives . TEACH (NCT00896051) was a randomized, open-label, two-arm Phase II trial to investigate the pharmacokinetic interaction between etravirine and atazanavir/ritonavir and safety and efficacy in treatment-experienced, HIV-1-infected patients. Methods . After a two-week lead-in of two nucleoside reverse transcriptase inhibitors (NRTIs) and atazanavir/ritonavir 300/100 mg, 44 patients received etravirine 200 mg bid with one NRTI, plus atazanavir/ritonavir 300/100 mg or 400/100 mg qd (n = 22 each group) over 48 weeks. Results . At steady-state etravirine with atazanavir/ritonavir 300/100 mg qd or 400/100 mg qd decreased atazanavir C min ⁡ by 18% and 9%, respectively, with no change in AUC 24 h or C max ⁡ versus atazanavir/ritonavir 300/100 mg qd alone (Day −1). Etravirine AUC 12 h was 24% higher and 16% lower with atazanavir/ritonavir 300/100 or 400/100 mg qd, respectively, versus historical controls. At Week 48, no significant differences were seen between the atazanavir/ritonavir groups in discontinuations due to adverse events (9.1% each group) and other safety parameters, the proportion of patients with viral load <50 copies/mL (intent-to-treat population, noncompleter = failure) (50.0%, atazanavir/ritonavir 300/100 mg qd versus 45.5%, 400/100 mg qd), and virologic failures (31.8% versus 27.3%, resp.). Conclusions . Etravirine 200 mg bid can be combined with atazanavir/ritonavir 300/100 mg qd and an NRTI in HIV-1-infected, treatment-experienced patients without dose adjustment.